God's continent : Christianity, Islam, and Europe's religious crisis - Jenkins, Philip, 1952- (Oxford ; New York : Oxford University Press, 2007)
What does the future hold for European Christianity? Is the Christian church doomed to collapse under the weight of globalization, Western secularism, and a flood of Muslim immigrants? Is Europe, in short, on the brink of becoming "Eurabia"? Though many pundits are loudly predicting just such a scenario, Philip Jenkins reveals the flaws in these arguments in God's Continent and offers a much more measured assessment of Europe's religious future. While frankly acknowledging current tensions, Jenkins shows, for instance, that the overheated rhetoric about a Muslim-dominated Europe is based on politically convenient myths: that Europe is being imperiled by floods of Muslim immigrants, exploding Muslim birth-rates, and the demise of European Christianity. He points out that by no means are Muslims the only new immigrants in Europe. Christians from Africa, Asia, and Eastern Europe are also pouring into the Western countries, and bringing with them a vibrant and enthusiastic faith that is helping to transform the face of European Christianity. Jenkins agrees that both Christianity and Islam face real difficulties in surviving within Europe's secular culture. But instead of fading away, both have adapted, and are adapting. Yes, the churches are in decline, but there are also clear indications that Christian loyalty and devotion survive, even as institutions crumble. Jenkins sees encouraging signs of continuing Christian devotion in Europe, especially in pilgrimages that attract millions--more in fact than in bygone "ages of faith."--Publisher
Your religion tomorrow -- Godless Europe? -- Faith among the ruins -- New Christians -- The Moor's return -- Making Muslims -- Young and old -- Revolutions at home -- Ultras -- Transforming Europe -- Transforming faith -- Europe's religions tomorrow.
BIBINDX
Keywords: Christianity and other religions -- Islam; Islam -- Relations -- Christianity; Europe -- Religion -- 21st century